THE ROLE OF COMMUNICATION MANAGEMENT THEORY IN THE SUSTAINABILITY OF SUBAK BASED ON THE TRI HITA KARANA CONCEPT UNDER TOURISM PRESSURE - Hadianto ego gantiano; Bagus Ade Ade Tegar Prabawa; I Nyoman Surpa Adisastra (International Journal of Social Studies, 2025)
This study examines the application of Communication Management Theory in the sustainability of Subak based on the Tri Hita Karana concept amid the pressure of mass tourism. Subak, as a socio-ecological system and a world cultural heritage, faces serious challenges due to land-use conversion, competition for water resources, and the commercialization of agricultural landscapes. These conditions affect not only ecological and economic aspects but also the social structure and communication patterns of the farming community. This study aims to analyze the role of communication in maintaining the sustainability of Subak and to explore the relevance of Communication Management Theory in understanding the existing social dynamics. The research adopts a qualitative method with an ethnographic approach based on a literature study using books and reputable scholarly journal articles as data sources. The data were analyzed interpretatively through thematic content analysis. The findings indicate that communication within Subak functions as a primary instrument in maintaining social order, managing conflict, aligning shared meanings, and coordinating collective action among farmers. The integration of Tri Hita Karana values into communication practices strengthens the social, spiritual, and ecological resilience of Subak. Thus, Communication Management Theory is proven to be a relevant analytical framework for understanding the sustainability of Subak in the face of modern tourism pressures.